Design, synthesis and antitumour activity evaluation of novel dolutegravir derivatives - Hou, Xi-Xi; Mao, Long-Fei; Guo, Yajie; Lou, Chaoxuan; Wang, Lan; Li, Rui-Fang; Wang, Huili; Li, San-Qiang; Yang, Jian-Xue (Frontiers in Pharmacology, 2023)
Based on the modification of the structure of dolutegravir, we introduced 1,2,3triazole moieties with different substituted groups and obtained a lot of novel dolutegravir derivatives. The activity of A549 cells treated with the derivatives was examined, and most compounds showed good inhibitory effects. Among them, compounds 4b and 4g were the most effective, and inhibited the growth of A549 cells with IC 50 values of 8.72 ± 0.11 µM and 12.97 ± 0.32 µM, respectively. In addition, compound 4g induced apoptosis and clonal suppression in A549 tumor cells. Compound 4g also activated the LC3 signaling pathway to induce autophagy in tumor cells, and activated the γ-H2AX signaling pathway to induce DNA damage in tumor cells.